Scientific Curiosity of Biology Teacher Candidate - Suhirman Suhirman; Yusuf Yusuf; Hunaepi Hunaepi; Muhammad Ikhsan (Yayasan Keluarga Guru Mandiri, 2022)
The purpose of this study was to identify the scientific curiosity of prospective Biological teachers based on gender. Scientific curiosity in this research consists of three components, namely 1) Practice Science, 2) Stretch, and 3) Embrace. The survey method used in this study involved 100 prospective students of education teachers as samples. Scientific curiosity data was collected using Science Curiosity in Learning Environments (SCILE) which has been declared reliable (Cronbach alpha: 0.91). Differences in the scientific curiosity of male and female were analyzed descriptively and statistically using t-test and Mann-Whitney test. The results showed that the scientific curiosity of science teacher candidates was in a good category, male and female teacher candidates were significantly different only in the science practice component (p: 0.020), while the stretching (p: 0.505) and embracing components (p : 0.05). : 0.185). no significant difference was found between male and female students